2017
DOI: 10.1530/rep-16-0265
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Binding Protein 1 (SBP1) autoantibodies in ovarian disorders and ovarian cancer

Abstract: Infertility is a risk factor for ovarian cancer (OvCa). The goal was to determine if antibodies to Selenium Binding Protein 1 (SBP1), an autoantibody we identified in patients with premature ovarian failure (POF), occurs in both infertility and OvCa patients, and thus could be associated with preneoplasia. Anti-SBP1 was measured by immunoassay against recombinant SBP1, in sera from OvCa (n=41), infertility (n=92) and control (n=87) patients. Infertility causes were POF, unexplained, irregular ovulation or endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
(97 reference statements)
0
11
0
1
Order By: Relevance
“…A study reported that a panel with four biomarkers [CA125, macrophage inhibitory factor (MIF), osteopontin (OPN), and anti-IL-8 autoantibodies] could identify 82.0% of OC with early stage compared to 65% with CA125 alone ( 35 ). It was demonstrated that the combination of CA125, anti-SBP1, and anti-TP53 greatly improved the sensitivity and specificity of OC identification with the AUC of 0.96 ( 36 ). From this study, the combination of anti-PDLIM1 AAb and CA125 could detect 79.2% patients with OC, which is statistically higher than when using CA125 or anti-PDLIM1 AAb alone.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that a panel with four biomarkers [CA125, macrophage inhibitory factor (MIF), osteopontin (OPN), and anti-IL-8 autoantibodies] could identify 82.0% of OC with early stage compared to 65% with CA125 alone ( 35 ). It was demonstrated that the combination of CA125, anti-SBP1, and anti-TP53 greatly improved the sensitivity and specificity of OC identification with the AUC of 0.96 ( 36 ). From this study, the combination of anti-PDLIM1 AAb and CA125 could detect 79.2% patients with OC, which is statistically higher than when using CA125 or anti-PDLIM1 AAb alone.…”
Section: Discussionmentioning
confidence: 99%
“…Based on research on the interdependence of endometriosis and disorders of the immune system, a number of abnormalities in the immune system in patients with endometriosis was postulated. The impaired function of T cells, B cells, and NK cells, the increased levels of various proinflammatory cytokines and angiogenetic factors such as IL-6, IL-1, and TNF- α , and the production of autoantibodies have been proved [1013].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Yu-Rice et al found a significantly more frequent presence of anti-SBP1 antibodies in the sera of women with ovulatory disorders (50.0 %, p = 0.007), idiopathic infertility (24.3 %, p = 0.02) and premature ovarian failure (28.0 %, p = 0.02) relatively to the control group. Moreover, the same authors noted a more frequent occurrence of antibodies in serous ovarian tumors and suggested that anti-SBP-1 can be used as a predictor of ovarian cancer in the future [115]. This conclusion seems quite logical, given that in a number of experimental studies performed much earlier, the ability of SBP1 to suppress tumor growth was noted [116; 117].…”
Section: Antibodies To Se-binding Protein-1 (Sbp-1)mentioning
confidence: 99%